How to do a penile urethroplasty using a novel self‐retaining penile retractor. Issue 1 (14th September 2022) - Flynn, Hannah; Joshi, Pankaj M.; Kulkarni, Sanjay Balwant; Desai, Devang
Abstract: Effective retraction and clear exposure of urethral tissue is essential in reconstructive penile surgery. The Joshi–Kulkarni retractor provides stable, bloodless operative exposure via non‐traumatic tissue compression at the base of penis. The self‐retaining design of this retractor also improves ergonomics thereby reducing surgeon fatigue. In this article, we describe how to do a penile urethroplasty by using the Joshi–Kulkarni penile retractor. Abstract : The Joshi–Kulkarni retractor is a valuable addition to the toolkit of genitourinary reconstructive surgeons. It provides stable, bloodless operative exposure via non‐traumatic tissue compression at the base of penis. This sturdy, self‐retaining retractor improves ergonomics and operative exposure, thereby reducing operative times, blood loss and iatrogenic tissue damage.